Análise da estabilidade global de edifícios com múltiplos pavimentos em concreto armado com diferentes tipos de lajes e inclusão de núcleos rígidos - Camicia, Rodrigo Junior da Motta (2017)
The use of different types of slabs in the execution of high buildings has been increasing a lot in recent years in the Brazilian market. The buildings have a bold and slender architecture, they bring to the engineering the challenge of executing a structure with different models and executive methods, and as a consequence arise the difficulties in guaranteeing the overall stability of the buildings. The choice of slab type and the inclusion of a rigid core in multi-floor building structures is an important choice, and global stability analysis of buildings are directly influenced by this choice. The evaluation of the global stability of reinforced concrete structures, normalized by the Brazilian standard ABNT NBR 6118: 2014, is performed through the global stability parameters parameter α (alpha) and coefficient γz (Range Z), in addition to the iterative P-Delta process. In this research, we tried to study the global stability in multi-floor buildings with different types of slabs and inclusion of rigid cores. For the modeling, the commercial CAD / TQS program was used. The results showed that the structure with solid slab was more rigid compared to structures with prefabricated slab and ribbed slab, obtaining lower values of Coefiente Gama Z and the inclusion of the rigid core considerably increased the rigidity of all structures analyzed.